Faktor-Faktor Yang Mempengaruhi Keputusan Pengambilan Pembiayaan Bank Wakaf Mikro Dengan Lingkungan Sebagai Variabel Moderasi - Faridhotul Mafruroh; Nafis Irkhami; Abdul Ghoni (ITB AAS INDONESIA Surakarta, 2022)
Indonesian people to be included in the bankable category, financial inclusion must be massive, one of OJK's solutions is the existence of a Micro Waqf Bank. The aims of this research are to know; 1.how does islamic financial literacy, gender, earning, and service quality influence the decision to do financing; 2. How does the environment strengthen or weaken the influence of Islamic financial literacy, gender, income, and service quality on decisions to finance. The research sample are customers in Bank Wakaf Micro Syubbanul Wathon Maslahah Magelang with incidental sampling method. There are 86 responden and the research data was analyzed using Moderation Regretion Analisis(MRA) with SPSS version 28.0.The results of this research showid that;1. islamic financial literacy, gender, earning, and service quality influence influencing financial decision;2. environment strengthen the relationship between Islamic financial literacy as much as 23.3%, gender 23.1%, income 22.6% and service quality 17.1% on the decision to do financing.